2010
DOI: 10.1007/s11010-010-0557-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ranolazine on fatty acid transformation in the isolated perfused rat liver

Abstract: It has been proposed that in the heart, ranolazine shifts the energy source from fatty acids to glucose oxidation by inhibiting fatty acid oxidation. Up to now no mechanism for this inhibition has been proposed. The purpose of this study was to investigate if ranolazine also affects hepatic fatty acid oxidation, with especial emphasis on cell membrane permeation based on the observations that the compound interacts with biological membranes. The isolated perfused rat liver was used, and [1-(14)C]oleate transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
2
9
2
Order By: Relevance
“…Even so, the lipolytic action of p-synephrine is an important component of some of its anabolic effects in the liver such as the stimulation of glucose synthesis, which depends, partly at least, on the oxidation of endogenous fatty acids as a means of supplying ATP and reducing equivalents [25] [26]. On the other hand, if p-synephrine is expected to mobilize fatty acids from other tissues (e.g., adipose tissue), no coordinated stimulation of their oxidation can be expected in the liver except that one given by its increased availability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, the lipolytic action of p-synephrine is an important component of some of its anabolic effects in the liver such as the stimulation of glucose synthesis, which depends, partly at least, on the oxidation of endogenous fatty acids as a means of supplying ATP and reducing equivalents [25] [26]. On the other hand, if p-synephrine is expected to mobilize fatty acids from other tissues (e.g., adipose tissue), no coordinated stimulation of their oxidation can be expected in the liver except that one given by its increased availability.…”
Section: Resultsmentioning
confidence: 99%
“…The arguments supporting this conclusion are as follows: 1) p-synephrine stimulates the hepatic triacylglycerol lipase (Figure 1), thus increasing the endogenous availability of nonesterified fatty acids to the point that a certain amount can even be released by the liver ( Figure 2); 2) psynephrine increases oxygen uptake also in the absence of any exogenous sub- 4) p-synephrine also increases oxygen uptake under gluconeogenic conditions (Table 1), a situation in which the oxidation of endogenous fatty acids has been demonstrated to provide a considerable part of the reducing equivalents to the mitochondrial respiratory chain, especially when glucose synthesis is stimulated, as it in fact occurs in the presence of p-synephrine [9] [25] [26]. p-octopamine also stimulates the hepatic triacylglycerol lipase and, thus, also increases the availability of endogenous non-esterified fatty acids.…”
Section: Effects Of P-synephrine On Fatty Acid Oxidationmentioning
confidence: 99%
“…Several potential mechanisms underlying ranolazine’s effect on glucose control have been examined. Ranolazine preserves pancreatic β-cell mass in streptozocin-treated mice by unclear molecular mechanisms (20), reduces glucagon secretion via inhibition of sodium channels (8), and diminishes fatty acid oxygenation in the liver, shifting the liver’s energy source from fatty acids to glucose (21). Ranolazine also increases steady-state metformin concentrations in the serum (22), and some of ranolazine’s effect on HbA1c seen in our study may be mediated by potentiation of metformin’s effect, though this mechanism would not explain ranolazine’s effect on HbA1c in patients without DM.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were accompanied by a reduction in the levels of acetyl-CoA in the heart tissue [4]. In the liver, which is the site of ranolazine biotransformation [9], it has been shown that ranolazine inhibits oleate net uptake (40% at 200 µM ranolazine) by diminishing the transfer of this fatty acid from the extracellular albumin site to the intracellular space [10]. No effect on the coefficient for intracellular sequestration of oleate was found.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, ranolazine also inhibits the extra oxygen consumption caused by oleate, as well as the extra ketogenesis induced by this substrate. It seems thus that in the liver ranolazine acts on fatty acid metabolism by at least two mechanisms: inhibition of cell membrane permeation and inhibition of the mitochondrial electron transfer via pyridine nucleotides [10]. The latter involves possibly the NADH dehydrogenase, but a direct effect on specific enzymes, especially β-hydroxybutyrate dehydrogenase, cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%